BAGAIMANA RENCANA MASA DEPANMU?: PENGARUH JENIS KELAMIN DAN KEPRIBADIAN TERHADAP MINAT SISWA DALAM MEMILIH JURUSAN PERGURUAN TINGGI - Rooswita Santia Dewi; Nadia Khairina; Dwi Nur Rachmah; Muhammad Syarif Hidayatullah (Jurnal Visi Ilmu Pendidikan)
Person's personality can affect what they might do in response to a particular circumstance or event. According to the study's findings, personality has an impact on a person's behavior, including their career decisions. Based on these conclusions, we want to identify the root cause by examining the impact of personality on interest in general election lectures based on gender and sex. 354 Senior High School students who were getting ready for university selection made up the study's sample. Respondents in the study This is student class XII (Science and Social Sciences) at school Senior High School (SMA) in South Kalimantan. Data were retrieved for more than 2 months and were nonparametric data. Collected data will be analyzed using analysis Chi-Square. The result shows that there wasn’t a significant influence between gender and personality to interest in election major lectures to students’ Senior High School. Besides, it is also shown that the percentage proportion highest interest student men nor women is type work Medical (MED) (28.2%). Whereas type work with enthusiasts smallest is Outdoor, Mechanical, and Practical (1.4%). Based on the findings on these research is known that interest is not only influenced by someone’s gender nor personality